Issues Arising from Weak Ecclesiological Concepts in the Modern Day Pentecostal Church, Part 1 - Toh, William (Asian Journal of Pentecostal Studies, 2019)
The article discusses biblical definition and Pentecostal understanding of a Church followed by a discussion of three Pentecostal ecclesiological concepts, Christological, Pneumatological and Sociological including some of the issues that can result from a weakened form of these concepts. Topics include Pentecostal theology of the Church, growth of the Charismatic and Pentecostal movement, and Christological Concept of the Church.